2023
DOI: 10.3389/fimmu.2022.1083780
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocytes: A key role in liver inflammation

Abstract: Hepatocytes, the major parenchymal cells in the liver, are responsible for a variety of cellular functions including carbohydrate, lipid and protein metabolism, detoxification and immune cell activation to maintain liver homeotasis. Recent studies show hepatocytes play a pivotal role in liver inflammation. After receiving liver insults and inflammatory signals, hepatocytes may undergo organelle damage, and further respond by releasing mediators and expressing molecules that can act in the microenvironment as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 105 publications
0
26
0
Order By: Relevance
“…42 Hepatocytes are the primary cellular constituents of the liver that plays crucial role in the metabolic processes of carbohydrate, lipid and proteins. 43 The kidney plays a significant role in the metabolism processes of carbohydrate, with approximate 40% of systemic glucose production occurring in the proximal tubule during periods of fasting and under stress conditions. In contrast, while the intestinal tract does contribute to the metabolic responses 44 and provides the heart with energy through oxidative metabolism, 45 there is currently no statistical evidence to support a significant involvement of fetal gut and heart in neonatal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…42 Hepatocytes are the primary cellular constituents of the liver that plays crucial role in the metabolic processes of carbohydrate, lipid and proteins. 43 The kidney plays a significant role in the metabolism processes of carbohydrate, with approximate 40% of systemic glucose production occurring in the proximal tubule during periods of fasting and under stress conditions. In contrast, while the intestinal tract does contribute to the metabolic responses 44 and provides the heart with energy through oxidative metabolism, 45 there is currently no statistical evidence to support a significant involvement of fetal gut and heart in neonatal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our investigative endeavors have been profoundly directed toward three distinct categories of rhythmically orchestrated cell types, namely, hepatocytes, adipocytes, and intestinal epithelial cells, all of which assume pivotal roles in physiological processes. Hepatocytes, which constitute the majority of liver mass, are central to an array of biochemical and metabolic functions 118 . Adipocytes, along with their secretory products, are involved in numerous physiological processes and significantly influence metabolic health 119,120 .…”
Section: Circadian Regulation Of Non‐immune Cell Functionmentioning
confidence: 99%
“…Hepatocytes, which constitute the majority of liver mass, are central to an array of biochemical and metabolic functions. 118 Adipocytes, along with their secretory products, are involved in numerous physiological processes and significantly influence metabolic health. 119 , 120 Intestinal epithelial cells, essential for food digestion, nutrient absorption, and maintaining intestinal epithelial homeostasis, play a vital role in responding to diseases.…”
Section: Circadian Regulation Of Non‐immune Cell Functionmentioning
confidence: 99%
“…During AIH pathogenesis, APC cells activate T lymphocytes by mispresenting liver autoantigens as foreign antigens to uncharacterized T lymphocytes (Longhi et al, 2021). As unconventional APC cells, the presence of MHC class II molecules on the surface of hepatocytes has resulted in an enhanced autoimmune response to AIH (Gong et al, 2022). In vitro studies have shown that low concentrations of butyrate, a gut microbial metabolite, inhibit the proliferation of CD4 + T and CD8 + T cells (Correâ-Oliveira et al, 2016).…”
Section: Disruption Of Immune Cell Homeostasismentioning
confidence: 99%